Mrs. Nyai as A Legislative Career Woman in the Tapal Kuda Region of East Java: The Perspective of Existential Feminism and Islamic Values - Shiddiqi, Hasbi Ash; Ch, Mufidah; Zenrif, M. Fauzan (STAI Publisistik Thawalib Jakarta, 2026)
This study examines the limited scholarly attention given to the role of Bu Nyai as legislators in the Tapal Kuda region through Simone de Beauvoir’s existential feminism. It aims to analyze the roles, positions, and domestic relations of Bu Nyai within the legislative sphere in Tapal Kuda, East Java. A qualitative case study approach was conducted in the Tapal Kuda region. Data were collected through interviews, observation, and document analysis, and were analyzed thematically using data triangulation to obtain an in-depth understanding of Bu Nyai’s roles in the legislature. The findings show that Bu Nyai's involvement reflects a significant transformation of pesantren women from the domestic sphere into the public political arena. Figures such as Neng Dana, Ninik, and Neng Ufa utilize religious social capital, education, and organizational networks to strengthen their political positions. From Simone de Beauvoir’s perspective, they experience a process of becoming that negotiates between immanence and transcendence, thereby challenging patriarchal structures. In addition to legislative, oversight, and budgeting functions, they also advocate for women’s issues, education, health, and community-based economic empowerment. This demonstrates the strengthening of autonomous political subjectivities among pesantren women in Indonesia’s public sphere. In conclusion, Bu Nyai represents a transformation toward more independent and empowered political actors capable of transcending traditional patriarchal boundaries in Tapal Kuda. This study contributes to existential feminist scholarship and supports more inclusive and gender-responsive public policy in Indonesia.